ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEMILIHAN BANK OLEH NASABAH TABUNGAN HAJI (STUDI KASUS: PESERTA BIMBINGAN MANASIK HAJI AZIZIAH KEC. MEDAN JOHOR) - Vera Erlinda; Haroni Doli H. Ritonga (Departemen Ekonomi Pembangunan USU, 2013)
This research deals with the impact factors on pilgrim candidate selection of pilgrim fund saving bank at aziziah hajj guidance bureau. The object of this study is to determine which factor most affect customers in choosing a bank. Those factors are the service, facilities and location. Respondents are 30 participants of Aziziah. The method used in this research is descriptive analysis by the form of frequency table. By using this method, the researcher will find the most impacted factor of bank choice. The result shows that the main reason customers choose the bank for pilgrim’s fund is the service factor. While the facilities and location become the second factor after service.